SUMO conjugation of STAT1 protects cells from hyperresponsiveness to IFNγ - Begitt, Andreas; Droescher, Mathias; Knobeloch, Klaus-Peter; Vinkemeier, Uwe (American Society for Hematology, 2011)
The biologic effects of IFNγ are mediated by the transcription factor STAT1. The activity of STAT1 is inhibited by small ubiquitin-like modifier (SUMO) conjugation. This occurs both directly through decreasing STAT1 tyrosine phosphorylation and indirectly by facilitating STAT1 dephosphorylation consequential to increased STAT1 solubility because of suppressed paracrystal assembly. However, the physiologic implications of SUMO conjugation have remained unclear. Here, we used fibroblasts and bone marrow–derived macrophages (BMMs) from knockin mice expressing SUMO-free STAT1 to explore the consequences of STAT1 sumoylation for IFNγ signaling. Our experiments demonstrated buffer property of paracrystals for activated STAT1, such that SUMO-mediated paracrystal dispersal profoundly reduced phosphorylation of STAT1, which affected both the activating tyrosine 701 and the transcription-enhancing serine 727. Accordingly, the curtailed STAT1 activity in the nucleus caused by SUMO conjugation resulted in diminished transcription of IFNγ-responsive genes; and increased the IFNγ concentration more than 100-fold required to trigger lipopolysaccharide-induced cytotoxicity in bone marrow–derived macrophages. These experiments identify SUMO conjugation of STAT1 as a mechanism to permanently attenuate the IFNγ sensitivity of cells, which prevents hyperresponsiveness to this cytokine and its potentially self-destructive consequences. This sets the mode of SUMO-mediated inhibition apart from the other negative STAT regulators known to date.